Dogmática funcionalista y política criminal: una propuesta fundada en los derechos humanos - Zúñiga Rodríguez, Laura (2018)
In this paper I intend to reflect on the inability of functionalist dogmatic currents to contain the ius puniendi of the State. I will also point out what are the reasons of the penal system itself that have led to give the legislator a carte blanche, which has led to an unbridled punitiveness, and what fundamentals are proposed to build a more rational criminal response. By reviewing the current situation of criminal dogmatics, the questions of the method and the object of study of this branch of knowledge, we come to the conclusion of an improper relativism of a knowledge that is intended to be scientific. The rational proposal against this relativism is a criminal policy based on human rights.